New Anatomic Anterolateral Ligament Reconstruction Used in a Complex Revision ACL Reconstruction - Luke V. Tollefson BS; Nicholas I. Kennedy MD; Robert F. LaPrade MD, PhD (SAGE Publishing, 2024)
Background: Anterior cruciate ligament reconstructions (ACLRs) are performed to restore knee biomechanics, increase knee stability, and slow the progression of osteoarthritis. After ACLRs, many patients still have residual anterolateral instability which is a risk factor for ACL graft failure. An anterolateral ligament reconstruction (ALLR) attempts to restore the native function of the anterolateral complex to augment the ACL. Performing an ALLR with an ACLR has been reported to reduce symptoms of instability and improve clinical outcomes. Indications: While no definitive indication for an ALLR has been set, current considerations include high posterior tibial slope >12°, revision ACLR, high-grade pivot shift, skeletally immature patients, hyperlaxity, and patients in high-level sports. Technique Description: The preoperative assessment includes a thorough physical examination with special attention paid to rotational laxity assessed via the pivot-shift examination. Imaging should include standard radiographic series (anteroposterior, posteroanterior flexion, lateral, and sunrise views), long-leg mechanical axis views to assess coronal plane alignment and standing lateral ACL stress radiographs to assess sagittal alignment and objective instability. The iliotibial band ALLR graft is harvested first. An 8-cm long by 1-cm wide strip of the inferior iliotibial band is harvested in a standard fashion, leaving the distal aspect attached to Gerdy's tubercle. An anchor is placed centered upon the native ALL distal tibial insertion. The native ALL femoral origin is identified at 4.7 mm posterior and proximal to the fibular collateral ligament, and a second suture anchor is placed at this point. Final fixation is performed after the final fixation of the ACLR graft. Results: A study by Pioger et al reported that patients with ACLR and ALLR had significantly less reoperation rate than patients with isolated ACLR, 8.9% versus 20.5% respectively. Lee et al found that a revision ACLR in combination with an ALLR was effective in reducing rotational laxity, which was assessed by the pivot-shift test. Discussion: We describe a technique for a new anatomic ALLR using the iliotibial band that attempts to restore the native ALL anatomy. This surgical technique effectively restores rotational laxity and improves knee stability. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.